CHARACTERISTICS OF SEA ICE ALGAL COMMUNITY AND THE PRIMARY PRODUCTION IN SAROMA KO LAGOON AND RESOLUTE PASSAGE, 1992 (EXTENDED ABSTRACT) (16th Symposium on Polar Biology) - クドウ, サカエ; KUDOH, Sakae (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper